(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
The psychological literature on the subject of human aggression suggests that aggression is common place in everyday life. The literature engages with human aggression predominantly from the standpoint of positivistic science which defines human aggression in simple terms, tries to discover its ’causes’, and suggest interventions that will prevent it. This assumes that aggression is the result of ’causes’ outside the control and awareness of the somewhat passive individual, and implies that all aggression is pathological. This paper critically outlines the current models of human aggression and then considers an existential-phenomenological critique. It is suggested that such an exploration will unfold possibilities for greater awareness and choice, for both practitioner and client.